Procuradorias municipais: isonomia e discriminação no texto constitucional - Silva, Cristiane Vieira de Mello e (2010)
The purpose of this study is to analyze the omission in article 132 of the Federal Constitution as of 1988, concerning the express non-inclusion of the City Attorneys in the panel of public careers and its reflections under the aegis of the isonomy principle. It examines the consequences of relegating one of the entities of the symmetric Federation The County to ostracism, advocating for the need of safeguarding this entity s constitutional autonomy and competence. In order to achieve its main purpose, this research approaches issues such as May an essential guarantee not integrate the constitutional text? Does the person of public law have essential rights? Can a federated entity prescind from the professional who pursues a State function or even delegate it through outsourcing (a function considered essential to Justice)? Does the interpretation under the terms of the Constitution in force manage to remedy the raised failure? The task of clearing the issues proposed in the course of the work aims to serve, in the academic sphere, the purpose of dealing scientifically with constitutional issues with practical effects, to avoid that the statutory procedure of the political phenomenon is not named and reduced to a sheet of paper (LASSALLE, 1946). The citizen, the great achievements reported in History (such as constitutionalism), social and State dynamics and the progress among federated entities can not allow this digression. It is intended, through this study, to contribute to the scientific research in the form of constitution and administration with a reflex for a concrete application in social and political sphere